(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
PD Mugi Jaya is one of the business units in the field of chicken procurement in Bandung. Products produced in the form of chicken sent to various restaurants in Bandung. PD Mugi Jaya can distribute 5,000 chickens to restaurants that become customers and sell the type of chicken in retail in Bandung. The need to evaluate the inventory procurement strategy in 2021 in order to obtain a minimum total cost. The evaluation begins by determining the data patterns formed from the request data from September 2019 to December 2020. The pattern formed is a random pattern, which is then done forecasting demand 2021 with the method of forecasting that has the smallest error value. The preferred forecasting method is the Double Exponential Smoothing method with a MAPE value of 43.6%. The forecasting results are processed by the method of procurement of lot sizing (existing), Economic Order Quantity (EOQ), and Silver Meal supplies. The method that managed to obtain the minimum total cost is the Silver Meal method with a total cost of Rp 23,725,500.